Abaca frontier the socioeconomic and cultural transformation of Davao, 1898-1941 - Dacudao, Patricia Irene; Ateneo de Manila University Press (Quezon City Ateneo de Manila University Press, 2023)
Abaca Frontier: The Socioeconomic and Cultural Transformation of Davao, 1898–1941 presents the story of how abaca, a crop processed for cordage, became itself the rope that tied Davao and its inhabitants to international networks of commerce, culture, and the colonial developmental project. Straddling transoceanic US history, while still firmly situated in Philippine studies, this book boldly incorporates global forces into the retelling of local history. The historical voices woven into its narrative are diverse—Bagobo traders, Spanish missionaries, American housewives, Filipino settlers, Japanese laborers, and so on—each of whom found themselves in the Davao region in the early twentieth century for different reasons, yet all shared some vision of its promise. Sympathetic of its historical subjects, this book shows how the frontier imaginaries of various actors mobilized multicultural collaboration and cohabitation in strikingly, perhaps uniquely, peaceful ways. Abaca Frontier thus tells a new and welcome story, standing apart from the narratives of conflict and dispossession that are familiar to scholars of plantation industries and of Mindanao. --Back cover.
Revision of the author's thesis (Ph. D)--Murdoch University.
Includes bibliographical references (pages 367-393) and index.
In English.
Keywords: Abaca industry -- Philippines -- History; Davao Region (Philippines) -- Economic conditions; Davao Region (Philippines) -- History; Davao Region (Philippines) -- Social conditions